Professional development with Visio 2000 - Edson, David A. (Sams, 2000)
Professional Development with Visio 2000 empowers you to create your own Visio solutions quickly and easily. Using client-proven methods, and the success of his training seminars worldwide, Visio insider David Edson provides you with an understanding of the Visio development platform, and guides you through the use of Visual Basic for Applications (VBA), enabling you to create your own Visio solutions. You will benefit from David's expert knowledge of topics including understanding Visio solutions, working with SmartShapes, customizing ShapeSheets, Visio VBA automation, Generating Visio Drawings with ActiveX Automation, and much more.